2013
DOI: 10.1161/circoutcomes.111.000058
|View full text |Cite
|
Sign up to set email alerts
|

The UK National Health Service

Abstract: Background— Social gradients in cardiovascular mortality across the United Kingdom may reflect differences in incidence, disease severity, or treatment. It is unknown whether a universal healthcare system delivers equitable lifesaving medical therapy for coronary heart disease. We therefore examined secular trends in the use of key medical therapies stratified by socioeconomic circumstances across a broad spectrum of coronary disease presentations, including acute coronary syndromes, secondary prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
2
22
1
Order By: Relevance
“…Koopman et al, showed that women less than 55 years of age were less likely to be prescribed a lipid lowering agent for primary prevention [35]. Hawkins et al demonstrated that the rate of prescriptions for secondary prevention in stable angina was 10% lower in younger women than men [36]. In the Virgo study, at 1 year, women <55 years were less likely to be on optimal therapy following a myocardial infarction due to a disparity in treatment initiation rather than treatment adherence despite more likely to have had a previous PCI [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Koopman et al, showed that women less than 55 years of age were less likely to be prescribed a lipid lowering agent for primary prevention [35]. Hawkins et al demonstrated that the rate of prescriptions for secondary prevention in stable angina was 10% lower in younger women than men [36]. In the Virgo study, at 1 year, women <55 years were less likely to be on optimal therapy following a myocardial infarction due to a disparity in treatment initiation rather than treatment adherence despite more likely to have had a previous PCI [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, recent analysis of treatment trends in MI patients in the United Kingdom during this same time period showed improvements in blood pressure and cholesterol levels as well as treatment rates in coronary heart disease secondary prevention. 33 …”
Section: Discussionmentioning
confidence: 99%
“…9,24 Our findings are also consistent with secondary prevention studies that report sex differences in treatment by age group. 10,13,25 A cross-sectional observational analysis of national data for the United Kingdom showed that prescribing rates for secondary prevention therapies were ≈10% lower among women than men <55 years. 10 A study investigating post-AMI use of statins in Denmark found that young men used more statins than young women but there were no sex differences in use in older patients.…”
Section: Treatment Initiationmentioning
confidence: 99%
“…10,13,25 A cross-sectional observational analysis of national data for the United Kingdom showed that prescribing rates for secondary prevention therapies were ≈10% lower among women than men <55 years. 10 A study investigating post-AMI use of statins in Denmark found that young men used more statins than young women but there were no sex differences in use in older patients. 25 A large database study of cardiovascular drug use in the Netherlands showed that younger women showed the lowest use of antithrombotics, statins, BBs, and other blood pressure-lowering drugs; they were also less likely to be on combination therapy than men (P>0.001).…”
Section: Treatment Initiationmentioning
confidence: 99%
See 1 more Smart Citation